Risk Factors for Heart Failure Among Pan-European Childhood Cancer Survivors: A PanCareSurFup and ProCardio Cohort and Nested Case-Control Study. Issue 1 (1st January 2023) - de Baat, Esmée C.; Feijen, Elizabeth A.M.; Reulen, Raoul C.; Allodji, Rodrigue S.; Bagnasco, Francesca; Bardi, Edit; Belle, Fabiën N.; Byrne, Julianne; van Dalen, Elvira C.; Debiche, Ghazi; Diallo, Ibrahima; Grabow, Desiree; et al.
Abstract : PURPOSE: Heart failure (HF) is a potentially life-threatening complication of treatment for childhood cancer. We evaluated the risk and risk factors for HF in a large European study of long-term survivors. Little is known of the effects of low doses of treatment, which is needed to improve current treatment protocols and surveillance guidelines. METHODS: This study includes the PanCareSurFup and ProCardio cohort of ≥ 5-year childhood cancer survivors diagnosed between 1940 and 2009 in seven European countries (N = 42, 361). We calculated the cumulative incidence of HF and conducted a nested case-control study to evaluate detailed treatment-related risk factors. RESULTS: The cumulative incidence of HF was 2% (95% CI, 1.7 to 2.2) by age 50 years. The case-control study (n = 1, 000) showed that survivors who received a mean heart radiation therapy (RT) dose of 5 to < 15 Gy have an increased risk of HF (odds ratio, 5.5; 95% CI, 2.5 to 12.3), when compared with no heart RT. The risk associated with doses 5 to < 15 Gy increased with exposure of a larger heart volume. In addition, the HF risk increased in a linear fashion with higher mean heart RT doses. Regarding total cumulative anthracycline dose, survivors who received ≥ 100 mg/m 2 had a substantially increased risk of HF and survivors treated with a lower dose showed no significantly increased risk of HF. The dose-response relationship appeared quadratic with higher anthracycline doses. CONCLUSION: Survivors who received a mean heart RT dose of ≥ 5 Gy have an increased risk of HF. The risk associated with RT increases with larger volumes exposed. Survivors treated with < 100 mg/m 2 total cumulative anthracycline dose have no significantly increased risk of HF. These new findings might have consequences for new treatment protocols for children with cancer and for cardiomyopathy surveillance guidelines.